2009
DOI: 10.21236/ada494347
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of Bacteria, Pollens, and Naturally Occurring Airborne Particles: Excitation/Emission Spectra

Abstract: Approved for public release; distribution unlimited. FOR OFFICIAL USE ONLYii REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…One example of this effect of the local environment is that the EEM from different biological materials are not necessarily the same in a dried aerosol as in solution, because the aerosols are often dry or somewhat dry (e.g., [32]). Fig.…”
Section: Fluorescent Molecules and Their Excitation-emission Matrix (mentioning
confidence: 99%
“…One example of this effect of the local environment is that the EEM from different biological materials are not necessarily the same in a dried aerosol as in solution, because the aerosols are often dry or somewhat dry (e.g., [32]). Fig.…”
Section: Fluorescent Molecules and Their Excitation-emission Matrix (mentioning
confidence: 99%
“…Strong tryptophan and weaker NADH peaks are frequently seen in bacteria fluorescence spectra (Hill et al, 2009), and N TRY would likely be larger if bacteria dominated the fluorescent aerosol. The relationship between N NADH and N TRY is also inconsistent with previous PBA measurements using the WIBS-3, both published and unpublished, where positive correlation was observed even when N NADH and N TRY differed significantly.…”
Section: The Nature Of the N Nadh Diurnal Cyclementioning
confidence: 99%
“…Laser induced fluorescence (LIF) based instruments are modern, easy-to-use tools for real-time bioaerosol detection (e.g., Hill et al, 1995;Pinnick et al, 1995;Ho, 2002;Jeys et al, 2007;Pöhlker et al, 2012). The LIF technique is an effective method for detecting biological molecules such as tryptophan, NADH and flavins that are present in microbe cells (Lakowicz, 2006;Hill et al, 2009). Saari et al (2013) demonstrated that bacterial and fungal spores may be distinguished from each other through their dissimilar fluorescence spectra.…”
Section: Introductionmentioning
confidence: 99%